2019
DOI: 10.1177/0018726719887220
|View full text |Cite
|
Sign up to set email alerts
|

Company towns and the governmentality of desired identities

Abstract: How do people living in a company town come to desire to work for the firm that controls it? Based on an in-depth case study of Volkswagen in Wolfsburg, Germany, we make two principal contributions. First, drawing on Foucault’s concept of governmentality we investigate the mechanisms of power within which desired identities are shaped. Desired identities, we argue, are one means by which organizations exercise control over local populations. Second, we examine the multiple interlocking discourses by which Volk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…These are accompanied by pleas to recognize the diversity of institutional settings, the existence of multiple and often competing identity discourses, the tensions, gaps and looseness inherent in them that permit multiple interpretations, and the scope that individuals have to blend, borrow, deform, corrupt and appropriate creatively distinct discourses for their own ends. Resistance in this sense ‘is understood as a constant process of adaptation, subversion and reinscription of dominant discourses’ by individuals intent on ‘knowing ourselves’ (Thomas and Davies, 2005: 687; see also Moonesirust and Brown, 2019). Identities, in the main, are regarded as imposed upon but not defined, shaped but not determined; continuously improvised and crafted by agile practitioners, they are accommodations negotiated within relations of power (Coupland and Spedale, 2020).…”
Section: The Identity Work Perspectivementioning
confidence: 99%
“…These are accompanied by pleas to recognize the diversity of institutional settings, the existence of multiple and often competing identity discourses, the tensions, gaps and looseness inherent in them that permit multiple interpretations, and the scope that individuals have to blend, borrow, deform, corrupt and appropriate creatively distinct discourses for their own ends. Resistance in this sense ‘is understood as a constant process of adaptation, subversion and reinscription of dominant discourses’ by individuals intent on ‘knowing ourselves’ (Thomas and Davies, 2005: 687; see also Moonesirust and Brown, 2019). Identities, in the main, are regarded as imposed upon but not defined, shaped but not determined; continuously improvised and crafted by agile practitioners, they are accommodations negotiated within relations of power (Coupland and Spedale, 2020).…”
Section: The Identity Work Perspectivementioning
confidence: 99%
“…Researchers have observed the insidious effects of seeking compliance through normative/concertive approaches (e.g. Kunda, 1992;Robertson and Swan, 2003), the impact of 'soft bureaucracy' (Courpasson, 2000), and the willingness to accept a disciplinary regime as the price for the elite status (Moonesirust and Brown, 2019), or on reflexive terms (Kamoche et al, 2014). The foregoing parallels the MTs in our study, who were prepared to sacrifice higher salaries (up to 20-30%) for the privilege of remaining valued elites en route to the higher echelons, and perceived their elite identity as rooted in the presumption of expertise and promise of leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Sacrificing career and better pay was a technology of the self which demonstrates the internalisation of discipline, and which for Gagnon and Collinson (2014) illustrates the anxiety to achieve the desired identities. While financial rewards are important coercive tools for bestowing the status of 'insiders' (Moonesirust and Brown, 2019), retention through the promise of better pay illustrates the effect of discourse through seduction and manipulation (see also Clegg et al, 2006). This reveals a complex picture where, on the one hand, individuals refused to be fashioned into 'corporate clones' (Brown and Lewis, 2011: 886), yet by succumbing to the seduction of better pay and the promise of an elite career, ultimately ended up fashioned into clones who were grateful for the opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of recent studies have suggested that forms of paternalism exist in a variety of contemporary workplaces. For example, the company town studied by Moonesirust and Brown (2021) shares many similarities with early paternalistic regimes in that management control extends beyond formal organisational boundaries into the private lives of employees. Studies on knowledge-intensive, professional service firms have also implied that these firms are highly paternalistic (as evidenced, for example, by their mentoring practices and alumni networks) yet with short-term employment and high turnover (e.g.…”
Section: Situating Workplace Relations: Lpt and Paternalismmentioning
confidence: 99%